Internet Addiction Status and Related Factors among Medical Students: A Cross-Sectional Study in Western Iran. Issue 4 (July 2023) - Khazaie, Habibolah; Lebni, Javad Yoosefi; Abbas, Jaffar; Mahaki, Behzad; Chaboksavar, Fakhreddin; Kianipour, Neda; Toghroli, Razie; Ziapour, Arash
Background: In recent years, Internet and social media technology use have emerged as an integral tool of human society, and the evolution of technological integration, cyberspace, and web-technology has become a common practice in educational institutions. Internet usage among students has played an indispensable role in learning behavior; however, the excessive usage of the internet and social media leads to internet addiction. This original study has performed a focalized scrutiny on revealing relationships between internet addiction and associated factors among the students of medicine, dentistry, and pharmaceutical departments. Methods: This descriptive and analytical study recruited medical students from the Self-governing Education Incubator of Kermanshah. This survey distributed questionnaires among the respondents' three departments, and this statistical data reported on 420 valid responses of the respondents. They represent first and second-semester medical students of the academic year 2017–2018. The study selected medical students by applying Cochran's Sample Size Formula through Stratified Random Sampling and cross-sectional research design. The survey has utilized a demographic questionnaire of Young's Internet Addiction Test (IAT) for the data collection. The study analyzed received data by using SPSS version 23 and performed the descriptive statistics, and analytical statistics (t-test and ANOVA). Results: The results of the present study established that the majority of subjects were female students (53.3%), and the average age was 23.84 ± 2.14, including the students of all departments. Besides, findings specified that the overall mean and standard deviation scores were 3.34 and ±0.88. Internet addiction revealed mean and the standard deviation score measured for all students 3.29 ± 0.73, 3.17 ± 0.92, and 3.57 ± 0.64 correspondingly. The survey results illustrated that medical students' internet addiction substantially correlated with demographic variables, such as age, marital status, the field of study, academic term, significant time of consuming the internet, the key reason of utilizing the internet, and daily usage of the internet ( p < .05). Conclusion: The results of the study specified that 25% of medical students showed internet addiction. The students are increasingly using the internet, and it has penetrated among students. The design and implementation of adequate educational programs and the application of internet-based efficiency interventions are essential for both knowledge acquisition and medical students' healthy behavior.